The Story of the War Gamelan Is A Story of Truth - Hendra Santosa; Nina Herlina Lubis; Kunto Sofianto; R.M. Mulyadi (Mudra Jurnal Seni Budaya, 2016)
Stories about gamelan used in warfare are regarded as a character in a fairy tale, a story ofthe past apocryphal. The slogan of history that says no document no historical is an expression that history should not be based solely on “people said" or a story that is not necessarily true, he should be based on the facts of historical events occurred, so that the necessary documents to uncover the historical events. A historical narrative method is needed in the process of developing the method known as historical methods. The ancient manuscripts as a source of literary history, many stores historical events related to culture, especially with the musical arts. In this article will be discussed is the word Bheri and Mrdangga of two ancient manuscripts that ofwhich have been translated into Indonesian by previous researchers.Keyword: gamelan, war gamelan, story, mredangga, bheri